NEW CONVERGENCE THEOREMS FOR COMMON FIXED POINTS OF A WIDE RANGE OF NONLINEAR MAPPINGS - Ibaraki, T.; Takeuchi, Y. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2018)
In this article, we present new convergence theorems for common fixed points of a wide range of nonlinear mappings in the Hilbert space setting.